Relatórios de estágio supervisionado: um mecanismo de transferência de tecnologia para os cursos de engenharia - Cruz, José Carlos da (2014)
The present study has takeninto account the reasoning of Sábato triangle and reports from Supervised Training Curriculum of Engineering Course at the University as a study tool to verify the possibility of becoming a mechanism for technology transfer. The general objective of this research was to verify whether the Supervised Training Curriculum Reports of Engineering Courses have been or could be mechanisms for technology transfer. It is believed that the collection, organization and dissemination of data obtained through the reports may cause a change on the behavior of the actors involvedin the Supervised Training process. In order to achieve such a goal it was chosen an applied qualitative research approach by considering the dynamic relationship between the real world and the subjective one. The research was documentary (Supervised Training Curriculum Reports) from Engineering Courses of Federal Technological University of Paraná - Campus CornélioProcópio. Interviews with supervisors teachers have been made in order to identify requirements to the work of guidance and supervision of professional training since such reports could facilitate the dialogue between Education Institutions and Labor Market. It is suggested a new way of “seeing” theSupervised Training Curriculum and its reports by innovating and providing the acquired information and knowledge as well as adapting the academic period to society as a whole.